Surface Analysis of Chain Joint Components after Tribological Load and Usage of Antiwear Additives. (5th May 2015) - Sappok, D.; Merz, R.; Sauer, B.; Kopnarski, M.
Abstract : Wear in chain joints leads to an increased clearance and thus an elongation of the entire chain which determines the lifetime of the chain. This particularly applies for chains that are used in timing chain drives. The aim of this study was to investigate especially the influences of lubricant additives and a contamination with carbon black on the tribological behavior of chain joint components and to correlate these influences to observable changes in topographical and chemical surface properties. A precisely defined contact and load situation is essential for generating a comparable series of samples for surface analyses. To meet this requirement, chain joint component samples from tests on a linear reciprocating model tribometer were used for the following analyses. But to connect the results to the realistic situation regarding the typical wear rates of the subjected chain types, suited experimental parameters were selected. Topographical, structural, and chemical characterization of the worn surface regions of the components were performed after the tribological loading. The results show the influence of the lubricant, the additive, and the contamination with carbon black especially on the chemical properties of the component surfaces.